Association of CTLA-4 Single Nucleotide Polymorphisms with Autoimmune Hypothyroidism in Iraqi Patients - Yassin, Alya H.; Al-Kazaz, Abdul-Kareem A.; Rahmah, Abbas Mahdi; Ibrahim, Taha Y. (Iraqi Journal of Science, 2022)
Genetic and environmental factors are believed to have a key role in the development and pathogenesis of autoimmune thyroid diseases (AITD). This study aimed to investigate the association between two CTLA-4 gene single nucleotide polymorphisms (SNPs) CT60/rs3087243 and CT61/rs11571319 with autoimmune thyroiditis in a sample of Iraqi patients. Seventy-five patients (67 females, 8 males) and eighty-eight subjects (79 females and 9 males) matched in age, gender, and ethnicity as a control group. Thyroid autoantibodies were present in females more than in males with a total positivity of anti-TPO of 92% and anti-TG positivity of57.3 %. Thyroid evaluation tests including T3, T4, and TSH were abnormal only in patients not receiving L-thyroxine treatment for autoimmune hypothyroidism, while patients on L-treatment and control subjects had normal results of these tests. CTLA-4 genotype frequencies were consistent with Hardy-Weinberg equilibrium (HWE) with no significant differences (p > 0.05) between the genotypes of patients and the control group. Analysis of CTLA-4 genotype and allele frequencies in patients and controls indicated the lack of significant differences among these frequencies except for allele G of rs3087243 which was associated significantly (P= 0.032) with the disease with OR of 1.62, while allele A can have a protective effect with OR of 0.66. Alleles of rs11571319 showed no significant ifferences despite the decreased frequency of G allele (83.33vs.87.5 %) and increased frequency of A allele (16.66vs.12.5%) in patients compared to controls. In conclusion, G allele of rs3087243 can be considered a risk factor for autoimmune hypothyroidism while noassociation was found regarding rs11571319 in the Iraqi population.